RP-HPLC METHOD DEVELOPMENT AND VALIDATION FOR SIMULTANEOUS ESTIMATION OF DICLOFENAC AND TOLPERISONE IN TABLET DOSAGE FORM - vemula, venkata raveendra babu; Sharma, Pankaj Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Objective: To develop a simple and cost effective reverse phase high performance liquid chromatography method for simultaneous estimation of Diclofenac and Tolperisone in tablet dosage form. Methods: Chromatography was carried out isocratically at 30Â°C Â± 0.5Â°C on an XDB C-18 column (4.6 x 150mm, 5Î¼ particle size) with a mobile phase composed Â ofÂ acetonitrile -phosphate Â buffer Â pH-3 Â (30:70% v/v) Â at Â a Â flow rate Â ofÂ 1.0 Â mL/min. DetectionÂ was carried out using a PDA detector at 260 nm. Validation parameters were studied as per ICH guidelines. Results: The retention times for Diclofenac and Tolperisone are 2.2 min and 4.7 min respectively. The linearity range for Diclofenac and Tolperisone are 12.5-125Âµg/mL and 37.5-375 Âµg/mL respectively. The percentage recoveries of Diclofenac and Tolperisone are 99.96% and 100.65% respectively. The correlation coefficients for both components are close to 1. Conclusion: This method is fast, accurate, precise and sensitive hence it can be employed for routine quality control of tablets containing both drugs in industries. Â Keywords: RP-HPLC, Diclofenac, Tolperisone, Simultaneous estimation. Â